Optimal shakedown of the thin-wall metal structures under strength and stiffness constraints = Optymalizacja przystosowania cienkościennych konstrukcji metalowych przy ograniczeniach ich nośności i sztywności - Alawdin, Piotr; Liepa, Liudas (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Classical optimization problems of metal structures confined mainly with 1st class cross-sections. But in practice it is common to use the cross-sections of higher classes. In this paper, a new mathematical model for described shakedown optimization problem for metal structures, which elements are designed from 1st to 4th class cross-sections, under variable quasi-static loads is presented. The features of limited plastic redistribution of forces in the structure with thin-walled elements there are taken into account.
Keywords: shakedown; thin-wall metal structures; strength; stiffness; optimization; mathematical programming; konstrukcje cienkościenne; konstrukcje metalowe cienkościenne; nośność; sztywność; optymalizacja; programowanie matematyczne